A Rot of Detached Durian Fruits Caused by Sclerotium rolfsii - Lim, Tong Kwee; Sijam, Kamaruzaman (1989)
A new fruit rot of fallen durian fruits was observed in the Uiversiti Pertanian Malaysia fruit orchard in Serdang, Selangor during the fruit ripening month of October, 1988. The rot was characterized by a dense, white, fan-shaped mat of coarse my celial strands of the causal fungus growing on a water-soaked, brown necrotic patch on the fruit in contact with decaying weed vegetation on the ground. The causal organism was identified as Sclerotium rolfsii. Presence of a thick weed undergrowth and its decaying leaf debris, and warm, moist conditions were shown to be important predisposing factors conducive to the development of the rot.